SIGNIFICANT REDUCTION OF BOTH PERIPAPILLARY AND SUBFOVEAL CHOROIDAL THICKNESS AFTER PANRETINAL PHOTOCOAGULATION IN PATIENTS WITH TYPE 2 DIABETES. Issue 10 (October 2018) - Kang, Hae Min; Lee, Na Eun; Choi, Jeong Hoon; Koh, Hyoung Jun; Lee, Sung Chul
Abstract : Purpose: To evaluate changes in peripapillary choroidal thickness (PCT) and subfoveal choroidal thickness (SFCT) after panretinal photocoagulation (PRP) for diabetic retinopathy. Methods: This retrospective interventional study included 59 treatment-naive eyes of 33 patients who underwent PRP and completed ≥12 months of follow-up. Peripapillary choroidal thickness and SFCT were measured at baseline and 1, 3, 6, and 12 months post-PRP. Differences between baseline and 12 months (ΔSFCT and ΔPCT) and percentage changes (ΔSFCT or ΔPCT/baseline × 100%) were determined. Results: Mean SFCT was 287.7 ± 76.7 μ m (139.0–469.0 μ m) at baseline and 225.8 ± 62.0 μ m (102.5–379.5 μ m) 12 months post-PRP ( P < 0.001). Mean PCT was 161.2 ± 16.5 μ m (75.3–308.1 μ m) at baseline and 128.4 ± 41.8 μ m (73.0–212.9 μ m) 12 months post-PRP ( P < 0.001). ΔSFCT was −61.3 ± 28.7 μ m (−139.5 to −17.0 μ m), and %SFCT was 21.2 ± 7.2% (6.8% to 36.1%). ΔPCT was −36.4 ± 23.2 μ m (−149.1 to 5.4 μ m), and %PCT was 22.4 ± 12.0% (2.5% to 62.6%). Diabetic retinopathy severity was the only factor significantly correlated with %SFCT (β = 0.500, P = 0.004) and %PCT (β = 0.152, P = 0.024). Conclusion: Both PCT and SFCT reduced significantly after PRP. Diabetic retinopathy severity was significantly correlated with post-PRP changes of peripapillary and SFCT. Abstract : In this study, both subfoveal and peripapillary choroidal thickness reduced significantly over the 12 months after panretinal photocoagulation for diabetic retinopathy. The severity of diabetic retinopathy was significantly correlated with the changes in choroidal thickness.